Anti-corrosion MgO nanoparticle-equipped graphene oxide nanosheet for efficient room-temperature H2S removal. Issue 35 (25th August 2022) - Xu, Hai; Pan, Yankai; Hu, Feng; Niu, Bo; Zhang, Yayun; Long, Donghui
Abstract : Enhanced room-temperature H2 S removal on homogenized metal oxide nanoparticle-loaded 2D carbon nanosheets is reported. Band gap of metal oxides and degree of their bands mixing with H2 S orbitals are crucial for anti-corrosion oxidation of H2 S. Abstract : Metal oxides are promising materials for catalytic oxidation of H2 S at room temperature, but their deficiencies are a low catalytic performance and tendency to corrode in acid reaction surroundings. Herein, we report a facile strategy to prepare a series of ultrafine metal oxide nanoparticles loaded on reduced graphene oxide (rGO) for efficient H2 S catalytic oxidation at room temperature. The hyper-dispersed nanoparticles prevent the stacking of rGO and maintain its two-dimensional sheet structure, thus breaking through the limits of traditional porous carbons with easy blockage of nanopores and low porosity, and thereby offering large sulfur storage depot. Additionally, higher density of alkaline sites is provided for catalytic reaction that synergistically enhances the desulfurization performance. Density functional theory calculation was employed for interpreting the involved mechanism, and we found that the MgO crystal, with a larger band gap and poorer degree of its bands mixing with H2 S orbitals, possesses lower reactivity towards H2 S, which corresponds to strong corrosion resistance. Hence, the MgO/rGO composite exhibits excellent catalytic activity with a breakthrough capacity of 3110 mg g −1, which is higher than that of its counterparts. The current work contributes new insights into the synergistic catalytic oxidation mechanism of H2 S by metal oxides and carbon-based composites, and provides a theoretical basis for the design and development of efficient room-temperature desulfurizers.